Mitral regurgitation in hypertrophic obstructive cardiomyopathy: The role of the edge‐to‐edge technique. Issue 10 (19th July 2021) - Lapenna, Elisabetta; Alfieri, Ottavio; Nisi, Teodora; De Bonis, Michele
Abstract: Mitral regurgitation in hypertrophic obstructive cardiomyopathy (HOCM) is mainly due to systolic anterior motion (SAM) and may be abolished in most of the patients by extended myectomy alone. However, a minority of HOCM patients may present mitral regurgitation due to organic mitral valve (MV) anomalies (such as MV leaflet prolapse, chordal rupture, leaflet cleft, and fibrosis) which need to be addressed. In addition, when the thickness of the interventricular septum is not particularly pronounced, shallow myectomy may not be enough to eliminate SAM and additional procedures have been proposed, including MV replacement, anterior leaflet plication/extension, reorientation of papillary muscles, secondary chordae cutting, and edge‐to‐edge technique. MV repair in the context of hypertrophic cardiomyopathy is certainly more challenging due to the suboptimal exposure of the MV related to the presence of a hypertrophic left ventricle and a not particularly dilated left atrium. The simplest, least time‐consuming repair technique should, therefore, be chosen. In this setting, the edge‐to‐edge technique has the great advantage of being an easy, quick, and reproducible procedure. The disease process of HOCM is not confined to the myocardium, but also involves the MV apparatus, which plays a critical role in dynamic left ventricular outflow tract (LVOT) obstruction. A comprehensive approach utilizing multimodality imaging, particularly echocardiography and cardiac magnetic resonance, has identified multiple abnormalities of the MV complex that have enhanced our understanding of the mechanisms of SAM and LVOT obstruction in HOCM.